Pengaruh Kualitas layanan, Prosedur pinjaman, dan Persepsi harga terhadap Keputusan Nasabah dengan Kepuasan Nasabah dalam melakukan Pembiayaan KUR - Atiek Elyghasyah; Santi Yustini (Jurnal Perbankan Syariah, 2025)
This research aims to analyze and test, both directly and indirectly, the influence of service quality, loan procedures, and price perception on customer decisions, with customer satisfaction as a mediating factor, in obtaining people's business credit financing at Bank Syariah Indonesia KCP. Tangerang Selatan. This study uses primary and secondary data, where the data collection method employs questionnaires distributed to people's business credit financing customers from 2021-2023, totaling 693 customers. In this study, the sample with successfully processed data consists of 87 respondents. The sampling technique used in this research is non-probability sampling, with a purposive sampling method. Data is analyzed using SmartPLS.4. The results of this study show that the variables of service quality, loan procedures, and price perception have a significant influence on customer decisions, while the customer satisfaction variable does not affect customer decisions. Additionally, the service quality variable has a significant influence on customer decisions through customer satisfaction and loan procedures, while price perception does not affect customer decisions through customer satisfaction in obtaining people's business credit financing.